A Bibliometric Analysis of the Electoral Studies journal - Iradhad Taqwa Sihidi; Dedik Fitrah Suhermanto; Danang Kurniawan (Journal of Government and Civil Society, 2023)
Elections are one of the important topics in the study of global democracy. This study aims to analyze scientific literature in the Journal of Electoral Studies as one of the highly reputable international journals from 2016 to August 2021. The data was analyzed using a bibliometric approach and visualization using VOSViewer and R Studio. This study took 618 articles from various international authors which showed that the electoral studies journal was consistently published with the most authors coming from the United States even though the origin of the university came from the Universiteit van Amsterdam Netherlands. Voting behavior and elections are two important keywords that often appear, indicating that these two issues are most often discussed by authors because they are considered to contribute greatly to electoral studies. These two keywords will also continue to be relevant in future election studies both in electoral studies journals and in other reputable journals because the development of the issue is very dynamic.Pemilu merupakan salah satu topik penting dalam kajian demokrasi global. Penelitian ini bertujuan melakukan analisis literatur ilmiah di Â Jurnal electoral Studies sebagai salah satu jurnal internasional bereputasi tinggi dari terbitan 2016 sampai dengan Agustus 2021. Data dianalisa dengan menggunakan pendekatan bibliometrik dan visualisasi menggunakan VOSViewer dan R Studio. Studi ini mengambil 618 artikel dari berbagai penulis internasional yang menunjukan bahwa jurnal electoral studies konsisten terbit dengan penulis terbanyak berasal dari amerika serikat meskipun untuk asal universitas berasal dari Universiteit van Amsterdam Belanda. Voting behavior dan elections adalah 2 kata kunci penting yang sering muncul yang menandakan bahwa kedua isu tersebut paling sering dibahas oleh para penulis karena dianggap sangat memberikan kontribusi dalam kajian kepemiluan. Kedua kata kunci tersebut juga akan terus relevan dalam kajian-kajian pemilu selanjutnya baik di jurnal electoral studies maupun di jurnal-jurnal bereputasi lainya karena perkembangan isunya yang sangat dinamis.Â